1997
DOI: 10.1071/s97032
|View full text |Cite
|
Sign up to set email alerts
|

Change in infiltration characteristics associated with cultivation history of soils in south-eastern Queensland

Abstract: Change in soil infiltration characteristics with cultivation can result in reduced soil water storage, increased runoff and erosion, and reduced crop production. We measured changes in infiltration characteristics associated with years of cultivation for 5 soil groups in south-eastern Queensland. Soils were grouped according to soil type and texture into Sodosols, light and heavy Vertosols, Red Ferrosols, and Red Chromosols/Kandosols. Soil infiltration characteristics were determined from measurements of perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 0 publications
3
22
1
Order By: Relevance
“…The reduction in slope of the water retention curve in the cropping zone after the implementation of CTF was indicative of improved rhizosphere conditions due to the removal of cyclic compaction and tillage. Connolly et al (1997) demonstrated increased infiltration, and Radford et al (1995a) showed improved soil water storage, soil animal populations and yield increases that could be included among the benefits of changes in the slope of the SWRC. The reduction of the slope of the curve is in agreement with the increased textural porosity found and with the redistribution of pore sizes in favour of the relative number of macropores.…”
Section: Measured Changes In Soil Water Characteristicsmentioning
confidence: 99%
“…The reduction in slope of the water retention curve in the cropping zone after the implementation of CTF was indicative of improved rhizosphere conditions due to the removal of cyclic compaction and tillage. Connolly et al (1997) demonstrated increased infiltration, and Radford et al (1995a) showed improved soil water storage, soil animal populations and yield increases that could be included among the benefits of changes in the slope of the SWRC. The reduction of the slope of the curve is in agreement with the increased textural porosity found and with the redistribution of pore sizes in favour of the relative number of macropores.…”
Section: Measured Changes In Soil Water Characteristicsmentioning
confidence: 99%
“…The cropping catchment was used as a resource to study the impacts on soil structure and subsequent crop performance of cattle grazing crop residues (Radford et al 1999). Connolly et al (1997) and Connolly (2000) used the site to study soil hydraulic properties. The cropping area adjoining C2 has hosted studies of fallow management (Lawrence et al 1994), wheat establishment , nutrient stratification , fertiliser and fallow management interactions (Cowie et al 1995), and soil mixing .…”
Section: Companion Projectsmentioning
confidence: 99%
“…through wetting and swelling and formation of surface seals due to instability of the soil under rainfall reduces infiltration rates (Smith et al 1984;Connolly et al 1997). Soil carbon in the surface 0.1 m ranges from 0.7 to 0.9%, although before 25 years of cultivation the value was~2% (Connolly et al 1997).…”
Section: Soil Typementioning
confidence: 99%
“…Soil carbon in the surface 0.1 m ranges from 0.7 to 0.9%, although before 25 years of cultivation the value was~2% (Connolly et al 1997). A summary of soil chemical and physical properties is provided in Table 1.…”
Section: Soil Typementioning
confidence: 99%
See 1 more Smart Citation